2019
DOI: 10.1002/chem.201903313
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pyridyl and N‐Methylpyridinium Analogues of Rosamines: Relevance of Solvent and Charge on Their Photophysical Properties

Abstract: A series of pyridyl analogues of rosamines was prepared by employing two methodologies: (i) the conventional‐heating condensation of a pyridinecarboxaldehyde with 3‐(diethylamino)phenol in propionic acid, and (ii) the novel ohmic‐heating assisted condensation under “on water” conditions, followed by oxidation. The 4‐pyridyl substituted rosamine was further converted into the N‐methylpyridinium derivative through N‐alkylation using methyl iodide. The influence of the position and cationization of the nitrogen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Both C⋅⋅⋅I − and C⋅⋅⋅O interactions are not very common and usually occur in electron deficient π‐systems. In 2Re(BiPy‐Me) 2 the carbon atoms adjacent to the positively charged nitrogen can obviously act as acceptors of electron density; a similar behavior has been previously described for the other N‐methylpyridinium containing compounds [54,55] …”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Both C⋅⋅⋅I − and C⋅⋅⋅O interactions are not very common and usually occur in electron deficient π‐systems. In 2Re(BiPy‐Me) 2 the carbon atoms adjacent to the positively charged nitrogen can obviously act as acceptors of electron density; a similar behavior has been previously described for the other N‐methylpyridinium containing compounds [54,55] …”
Section: Resultssupporting
confidence: 68%
“…In 2Re(BiPy-Me) 2 the carbon atoms adjacent to the positively charged nitrogen can obviously act as acceptors of electron density; a similar behavior has been previously described for the other N-methylpyridinium containing compounds. [54,55] Structure and composition of these complexes in solution were elucidated by ESI mass-spectrometry and NMR spectroscopy. The mass-spectra of 2Re(Py) 2 , 2Re(Pz) 2 , 2Re(BiPy) 2 and 2Re(BiPy-Me) 2 display dominant signals of molecular ions with m/z values and isotopic patterns corresponding to the [(N N)Re (CO) 3 (L) 2 )] + stoichiometry (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, our work group designed a series of pyridyl analogs of rosamines (rhodamine derivatives lacking the carboxylic group at position 2′ of the benzenic ring) and studied the influence of solvent and charge on their photophysical properties [30]. It was found that the structural variation involving the position of the N-atom in the pyridine did not influence the absorption and fluorescence properties of dyes, the same could not be said about the charge -the introduction of a positive charge at the N-atom (18) in the pyridinium analog promoted a significant bathochromic shift in the absorption and fluorescence quenching, both effects associated to d-PET mechanism.…”
Section: Sensing Applicationsmentioning
confidence: 99%
“…The low fluorescence of the corresponding pyronin‐pyridinium hybrid structure was explained in terms of oxidative photo‐induced electron transfer (d‐PeT) process from the excited state of fluorescent pyronin group to the N ‐alkylpyridinium substituent LUMO (Figure 1). [22] Analyte‐triggered self‐immolative N ‐dealkylation process leads to the release of strongly fluorescent rosamine with pyridine unit, the effects of d‐PeT being prohibited. Several biomarkers including enzymes (nitroreductase, NTR), [21c] gasotransmitters (hydrogen sulfide, H 2 S) [21a,b] and ROS (hydrogen peroxide, H 2 O 2 ) [21b] have been successfully detected in solution and in cellular imaging, using this reaction‐based approach.…”
Section: Introductionmentioning
confidence: 99%